The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1002/recl.19821010102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thiazoles and imidazoles from isothiocyanates and tosylmethyl isocyanide. Base‐induced ring transformation of 5‐amino‐1,3‐thiazoles to imidazole‐5‐thiols

Abstract: Base‐induced cycloadditions of tosylmethyl isocyanide to a series of isothiocyanates have been investigated. Depending on the reaction conditions, thiazoles 5 and/or imidazoles 7 are obtained, with the thiazoles, in particular, being obtained with high regiospecificity. During the course of this work a high‐yield ring transformation of 5‐amino‐1,3‐thiazoles (5) to imidazole‐5‐thiols (7) was discovered, which has not been previously reported. A number of reactions of 7 are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…The injection temperature of 40 °C used in method 2b gave a good yield of erucin. This observation is supported by reports of isothiocyanates getting converted into thiazole and isothiazole at high temperature as reported by Van Nispen and others () and Mukerjee and Ashare ().…”
Section: Resultssupporting
confidence: 87%
“…The injection temperature of 40 °C used in method 2b gave a good yield of erucin. This observation is supported by reports of isothiocyanates getting converted into thiazole and isothiazole at high temperature as reported by Van Nispen and others () and Mukerjee and Ashare ().…”
Section: Resultssupporting
confidence: 87%
“…A literature search showed that 4-tosyl-1-arylimidazoles were already reported via different synthetic strategies. For example, they could be prepared by reacting arylazasulfones 5 with TosMIC or via oxidation of dilithiated 1-phenyl-4-tosyl-1 H -imidazole-5-thiol 6 with alkaline potassium ferricyanide or, finally, via reaction between aryl formamidate 7 or aryl formamidines and TosMIC in the presence of sodium hydride (Figure ).…”
mentioning
confidence: 99%